Instagram Utilization as User Generated Content in Promoting Local Culinary - Ratna Santika, Yuniarti; Chamidah, Nurul; sapari, Yusuf (Jurnal Toursci, 2024)
Promoting anything is one kind of communication that leverages social media and breakthroughs in IT. Information-gathering, public appeal, and influence-peddling are the goals of promotional activities. Informational, persuasive, and reminder campaigns are the goals of promotion. One app for sharing images or videos is called Instagram. Friends on Facebook can follow us on Instagram thanks to a feature of Instagram that is integrated into Facebook. The capabilities that Instagram offers its users are rather extensive. A user's creation of content and subsequent sharing on a platform of their choosing is known as user-generated content. Users utilize user-generated content to spread knowledge, advertise a company or product, and sometimes even attract attention and encourage other users to purchase. The Instagram account@kulinercirebon served as the study's subject. A food Instagram account, @kulinercirebon, highlights Cirebon's excellent food. Utilizing a qualitative research method with a descriptive approach, the study's objectives were to ascertain the @kulinercirebon account owner's creative process in optimizing Instagram accounts and the optimization of Instagram's use as a medium for Cirebon culinary promotion. The study yielded the following research findings: the process by which creators create promotional content is split into three stages: pre-production, content creation, and post-production. The best way to maximize Instagram's potential as a promotional tool is to take advantage of its features, which include captions, hashtags, video reels, Instagram feeds with multiple photos and comment features.